PHARMACEUTICAL NANOTECHNOLOGY FOR IMPROVING BIOAVAILABILITY AND THERAPEUTIC EFFICACY - Fatima Ahmed; Ali Omar; Muntasir Muntasir (Journal of Biomedical and Techno Nanomaterials, 2026)
Pharmaceutical nanotechnology has emerged as a promising approach to enhance the bioavailability and therapeutic efficacy of drugs. Many drugs suffer from poor solubility, limited absorption, and rapid metabolism, leading to suboptimal therapeutic outcomes. Nanotechnology-based drug delivery systems offer solutions to these challenges by improving the stability, solubility, and controlled release of pharmaceuticals. This study explores the use of nanotechnology in the design and development of drug delivery systems aimed at enhancing bioavailability and optimizing therapeutic efficacy. The primary objective is to evaluate the effectiveness of various nanocarriers, including liposomes, dendrimers, and polymeric nanoparticles, in improving drug solubility and ensuring targeted delivery. The research employs in vitro and in vivo models to assess drug release profiles, absorption rates, and pharmacokinetic properties. The results demonstrate that nanotechnology-based systems significantly improve drug bioavailability and extend therapeutic efficacy by providing controlled and sustained drug release, reducing side effects, and enhancing cellular uptake. In conclusion, pharmaceutical nanotechnology offers a powerful strategy to overcome the limitations of conventional drug delivery systems, providing a pathway for more effective treatments in various therapeutic areas.